Increase In Company Value Based On Investment Decisions, Company Size, And Sustainability Debt With Profitability As Mediation Variables - Hani’ah, Khoiriana Nur; Widyakto, Adhi; Fresiliasari, Oktavie (Sapta Arga Nusantara, 2025)
This study aims to determine the influence of investment decisions, company size, and debt policy on company value with profitability as a mediating variable for publicly listed manufacturing companies on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The data source for this research was obtained from annual financial reports and BEI statistics. The research population consisted of 458 manufacturing companies, and by using purposive sampling techniques, a sample of 113 companies was selected. Data analysis was conducted using the SmartPLS tool. The results of this study prove that the Price Earning Ratio (PER) has a significantly positive effect on profitability, Size has a significantly positive effect on profitability, the Debt to Equity Ratio (DER) has a significantly positive effect on profitability, the Price Earning Ratio (PER) has a significantly positive effect on Price to Book Value (PBV), Size has a significantly positive effect on Price to Book Value (PBV), DER has a significantly positive effect on Price to Book Value (PBV), Return on Equity (ROE) has a significantly positive effect on Price to Book Value (PBV), the Price Earning Ratio (PER) has a significantly positive effect on Price to Book Value (PBV) and Return on Equity (ROE) as an intervening variable, Size does not have an effect on Price to Book Value (PBV) and Return on Equity (ROE) as an intervening variable, and the Debt to Equity Ratio (DER) has a significantly positive effect on Price to Book Value (PBV) and Return on Equity (ROE) as an intervening variable.